Effect of right ventricular free wall longitudinal strain on all-cause death in patients with isolated severe tricuspid regurgitation and atrial fibrillation - Ogawa, Mana; Kuwajima, Ken; Yamane, Takafumi; Hasegawa, Hiroko; Yagi, Nobuichiro; Shiota, Takahiro (Frontiers in Cardiovascular Medicine, 2023)
Background With the aging population and advanced catheter-based therapy, isolated tricuspid regurgitation (TR) with atrial fibrillation (AF) has gained increased attention; however, data on the prognostic effect of isolated TR with AF are limited because of the small number of patients among those with severe TR. Recently, right ventricular (RV) longitudinal strain by two-dimensional speckle-tracking echocardiography has been reported as an excellent indicator of RV dysfunction in severe TR. However, the prognostic implications of RV longitudinal strain in isolated severe TR associated with AF remain unclear. Therefore, this study aimed to reveal the prognostic value of this index in this population. Methods We retrospectively studied patients with severe isolated TR associated with AF in the absence of other etiologies in the Cedars-Sinai Medical Center between April 2015 and March 2018. Baseline clinical and echocardiographic data were studied including RV systolic function evaluated by RV free wall longitudinal strain (FWLS) and conventional parameters. All-cause death was defined as the primary endpoint. Results In total, 53 patients (median age, 85 years; female, 60%) with a median follow-up of 433 (60–1567) days were included. Fourteen patients (26%) died, and 66% had right heart failure (RHF) symptoms. By multivariable analysis, reduced RVFWLS was independently associated with all-cause death. Patients with RVFWLS of ≤18% had higher risk of all-cause death adjusted for age (log-rank P = 0.030, adjusted hazard ratio 4.00, 95% confidence interval, 1.11–14.4; P = 0.034). When patients were stratified into four groups by RHF symptoms and RVFWLS, the group with symptomatic and reduced RVFWLS had the worst outcome. Conclusion Reduced RVFWLS was independently associated with all-cause death in patients with isolated severe TR and AF. Our subset classification showed the worst outcome from the combination of RHF symptoms and reduced RVFWLS.